2018
DOI: 10.1124/jpet.118.249326
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Mechanisms and a Rational Combinational Application of Carboxyamidotriazole in Fighting Pancreatic Cancer Progression after Chemotherapy

Abstract: The anticancer and anti-inflammatory effects of carboxyamidotriazole (CAI) have been demonstrated in several studies, but the underlying mechanisms remain to be elucidated. This study showed that CAI caused metabolic reprogramming of pancreatic cancer cells. The inhibition of mitochondrial oxidative metabolism by CAI led to increased glutamine-dependent reductive carboxylation and enhanced glycolytic metabolism. The presence of environmental substances that affect cellular metabolism, such as glutamine and pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
8
0
4
Order By: Relevance
“…On the contrary, the selective influence of [1,2,3] activity below moderate (mostly active on NCI-H522 Lung Cancer cell line) ( Table 1). In general, it can be concluded that the replacement of the amide moiety at position 4 of 1h-1,2,3-triazole leads to a decrease or loss of its anticancer activity.…”
Section: Scheme Synthesis Of 5-amino-1-aryl-1h-123-triazole Scaffoldsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, the selective influence of [1,2,3] activity below moderate (mostly active on NCI-H522 Lung Cancer cell line) ( Table 1). In general, it can be concluded that the replacement of the amide moiety at position 4 of 1h-1,2,3-triazole leads to a decrease or loss of its anticancer activity.…”
Section: Scheme Synthesis Of 5-amino-1-aryl-1h-123-triazole Scaffoldsmentioning
confidence: 99%
“…1) capable of binding to and inhibiting of the non-voltage-operated Ca 2+ channels and blocking cellular Ca 2+ influx and release, cause a disruption of calcium channel-mediated signal transduction and inhibition of vascular endothelial growth factor signalling, endothelial proliferation, and angiogenesis [1]. This agent is also widely used in cancer therapy [2][3][4]. Carboxyamidotriazole inhibits growth of H345 small cell lung cancer cells via VEGF-dependent pathway.…”
mentioning
confidence: 99%
See 3 more Smart Citations